Rare Plasmacytoid Urothelial Carcinoma of the Bladder: Two Case Reports - Devrim, Tuba; Atac, Fatih; Altunkaya, Canan; Ozbek, Ayse; Ozdemir, Gulhan; Eryol, Merve (Urology Journal, 2019)
Plasmacytoid urothelial carcinoma is a rare and aggressive form of urothelial carcinoma characterized with delayed presentation and poor prognosis. Very few cases of this carcinoma have been reported in the literature. Here, we report and discuss two cases of bladder plasmacytoid urothelial carcinoma of a 57-year-old male presented with renal colic, and a 33-year-old female presented with macroscopic hematuria. Pathologic examinations of the transurethral biopsies revealed urothelial carcinoma with plasmacytoid appearance. Subsequently, immunohistochemical evaluation showed positive expression of epithelial markers and CD138. Additionally, losing of the membranous expression of E-cadherin verified the diagnosis of plasmacytoid urothelial carcinoma.